Catalytic dehydrogenation of propane by carbon dioxide: a medium-temperature thermochemical process for carbon dioxide utilisation - Du, X; Yao, B; Gonzalez-Cortes, S; Kuznetsov, V; AlMegren, H; Xiao, T; Edwards, P (Royal Society of Chemistry, 2015)
The dehydrogenation of C3H8 in the presence of CO2 is an attractive catalytic route for C3H6 production. In studying the various possibilities to utilise CO2 to convert hydrocarbons using the sustainable energy source of solar thermal energy, thermodynamic calculations were carried out for the dehydrogenation of C3H8 using CO2for the process operating in the temperature range of 300-500 °C. Importantly, the results highlight the enhanced potential of C3H8 as compared to its lighter and heavier homologues (C2H6 and C4H10, respectively). To be utilised in this CO2 utilisation reaction the Gibbs free energy (ΔrG) of each reaction in the modelled, complete reacting system of the dehydrogenation of C3H8 in the presence of CO2 also indicate that further cracking of C3H6 will affect the ultimate yield and selectivity of the final products. In a parallel experimental study, catalytic tests of the dehydrogenation of C3H8 in the presence of CO2 over 5 wt%-Cr2O3/ZrO2 catalysts operating at 500 °C, atmospheric pressure, and for various C3H8 partial pressures and various overall GHSV (Gas Hourly Space Velocity) values. The results showed that an increase in the C3H8 partial pressure produced an inhibition of C3H8 conversion but, importantly, a promising enhancement of C3H6 selectivity. This phenomenon can be attributed to competitive adsorption on the catalyst between the generated C3H6 and inactivated C3H8, which inhibits any further cracking effect on C3H6 to produce by-products. As a comparison, the increase of the overall GHSV can also decrease the C3H8 conversion to a similar extent, but the further cracking of C3H6 cannot be limited.